Hope Family Program (PKH) for Poor of Family in Pekalongan Regency - Risqiana, Eky; Suyahmo, Suyahmo; Handoyo, Eko (JESS (Journal of Educational Social Studies), 2019)
The problem that is happening almost in every country is poverty. Some policies have been taken by the government for poverty alleviation, such as the Hope Family Program (PKH) that has existed since 2007. The problem in the case study is (1) what is the form of PKH assistance? (2) what is the role of PKH’s human resources? (3) the effect of PKH aid on poor families? The aim is to analyze the forms of PKH assistance, the role of PKH’s human resources and the impact of the PKH in Wonopringgo, Pekalongan Regency. The research method used is qualitative with the research design of the case study. The population in this study were PKH’s KPM, PKH's human resources, the village government. Data collection techniques through observation, interview and documentation. Validation of data through triangulation techniques. The results show that PKH’s KPM not only receives cash assistance but also complementary assistance. The role of PKH is to examine the various commitments of PKH participants as obligations that must be met. As a result, on the one hand it can make people realize their independent life, but on the other hand there are still people who are mentally poor.